Antīğān, un toponyme ibadite chez al-Idrisi - Prevost, Virginie (Al-Andalus Magreb, 2007)
In his short description of the western part of the island of Jerba, al-Idrīsī (in his K. Nuzhat al-Mushtāq fī Ikhtirāq al-Āfāq) mentions Antījān. This toponym is well known by the Ibāḍite historians since the first Jerban Ḥalqa was founded at this place at the end of the 11th century.
Keywords: Monuments -- Djerba; Tîwâjin, mosquée (Tîwâjin, Djerba)